Spectrophotometric Method for the Determination of Paracetamol - Shrestha, Buddha Ratna; Pradhananga, Raja Ram (Journal of Nepal Chemical Society, 2009)
Paracetamol with 1-napthol or resorcinol gave azodye and the concentration of paracetamol was investigated spectrophotometrically. The azodyes formed with both 1-napthol and resorcinol as coupling agents follow Lambert Beer’s law in the range of 0 to 10 µgmL-1 of paracetamol. The molar absorptivity and Sandell’s sensitivity for azodye coupled with 1-napthol were found to be 1.68×104 Lmol-1cm-1 and 9.0 ngmL-1cm-2, respectively. The molar absorptivity and Sandell’s sensitivity for azodye coupled with resorcinol were found to be 2.86×104 Lmol-1cm-1 and 5.3 ngmL-1cm-2, respectively. Both coupling agents had been applied successfully in the analysis of paracetamol in pharmaceutical preparation. The relative standard deviation for all five samples ranged from 2.2-6.4% at 95% confidence. The percentage recoveries were found to range from 97.8 to 103.4. Both methods used in the present study may be applied to the determination of trace amount of paracetamol in different clinical samples. Keyword: Paracetamol; Spectrophotometric; 1-napthol; Resorcinol DOI: 10.3126/jncs.v24i0.2389 Journal of Nepal Chemical Society Vol. 24, 2009 Page: 39-44